Naphthalene Exchange in [Re(η6‐napht)2]+ with Pharmaceuticals Leads to Highly Functionalized Sandwich Complexes [M(η6‐pharm)2]+ (M=Re/99mTc). Issue 5 (13th December 2021) - Nadeem, Qaisar; Battistin, Federica; Blacque, Olivier; Alberto, Roger
Abstract: Bis‐arene sandwich complexes are generally prepared by the Fischer‐Hafner reaction, which conditions are incompatible with most O‐ and N‐ functional groups. We report a new way for the synthesis of sandwich type complexes [Re(η 6 ‐arene)2 ] + and [Re(η 6 ‐arene)(η 6 ‐benzene)] + from [Re(η 6 ‐napht)2 ] + and [Re(η 6 ‐napht)(η 6 ‐benzene)] +, with functionalized arenes and pharmaceuticals. N‐methylpyrrolidine (NMP) facilitates the substitution of naphthalene with the incoming arene. A series of fully characterized rhenium sandwich complexes with simple arenes, such as aniline, as well as with active compounds like lidocaine and melatonin are presented. With these rhenium compounds in hand, the radioactive sandwich complexes [ 99m Tc(η 6 ‐pharm)2 ] + (pharm=pharmaceutical) can be unambiguously confirmed. The direct labelling of pharmaceuticals with 99m Tc through η 6 ‐coordination to phenyl rings and the confirmation of the structures with the rhenium homologues opens a path into molecular theranostics. Abstract : To overcome the limits of the Fischer‐Hafner reaction, [Re(η 6 ‐napht)2 ] + and [Re(η 6 ‐napht)(benzene)] + have been used to prepare sandwich complexes [Re(η 6 ‐arene)2 ] + and [Re(η 6 ‐arene)(η 6 ‐benzene)] + . NMP is used to promote the substitution of naphthalene with simple arenes as well as with active compounds like lidocaine and melatonin. This compound can be used to unambiguously confirm the radioactive sandwich complexes [ 99m Tc(η 6 ‐pharm)2 ] + .